Characterization of chitosan-spinacia oleracea films and its application as gas sensor - Chandrasakaran, Devi Shantini (School of Materials Engineering, 2016)
The research objectives are to study the effects of chitosan concentration, chitosan- spinacia oleracea ratio on microstructure, electrical, and thermal properties of chitosan films (CSF) and chitosan-spinacia oleracea films (CS-SPOF); to study the effects of chitosan concentration, chitosan- spinacia oleracea ratio, electrochemical deposition voltage and electrochemical deposition time on sensing properties of chitosan films sensors (CSFS) and chitosan-spinacia oleracea film sensors (CS-SPOFS); to study the sensing properties of chitosan film sensors (CSFS) and chitosan- spinacia oleracea film sensors (CS-SPOFS) toward ammonia, acetone, toluene and hexanal.